NHC/B(OH)3-mediated C3-selective acylation of unprotected monosaccharides: mechanistic insights and toward simpler/greener solutions - Jin, Jiamiao (2024)
Selective acylation of saccharides is an important basic transformation in saccharide chemistry. Synthetic strategies and protocols for saccharides can reach broad users when reagents are simple (inexpensive and readily available), green, and easy to handle. Herein, we disclose that the simplest boric acid, B(OH)3, can work as an effective promoter for C3-OH selective acylation of unprotected monosaccharides under the catalysis of a readily available N-heterocyclic carbene catalyst. Solvents such as THF from untreated commercial sources can be directly used. Mechanistically, the boric acid plays multiple roles in benefiting reaction yields and regioselectivities, including solubilizing the saccharide substrates by forming borate esters with the saccharides, shielding the C6-OH unit of the saccharides from acylation, and enhancing the selectivity between C3-OH and C2-OH reactions. We also found that the solvent has a profounder effect on the reaction yield and selectivity than the base. Selectively acylated saccharide products can be easily obtained with good-to-excellent yields and gram scales. Our study will encourage the further development of new synthetic strategies for saccharides that can reach beyond laboratory scales and to scientists not necessarily with expertise in organic synthesis. Compared to previous methods using aryl and alkyl boronic acids as modulating reagents, the use of boric acid provides a greener solution economically and environmentally.